2017
DOI: 10.3762/bjnano.8.165
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and intracellular accumulation of diamond nanoparticles – a metabolic and cytotoxic study

Abstract: Diamond nanoparticles, known as nanodiamonds (NDs), possess several medically significant properties. Having a tailorable and easily accessible surface gives them great potential for use in sensing and imaging applications and as a component of cell growth scaffolds. In this work we investigate in vitro interactions of human osteoblast-like SAOS-2 cells with four different groups of NDs, namely high-pressure high-temperature (HPHT) NDs (diameter 18–210 nm, oxygen-terminated), photoluminescent HPHT NDs (diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The medical use of NDs is probable because of their low cytotoxicity and high biological activity [9]. Several authors have reported a lack of toxic effects that manifest in the forms of inflammation and activation of macrophages [10], and symptoms of systemic toxicity after ND treatment in rats [11,12], but have also noted uptake and intracellular accumulation of NDs [13], activation of cell death (both apoptotic and necrotic) [14], and redox homeostasis disorders [15]. Diamond nanoparticles were also tested for their application in cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The medical use of NDs is probable because of their low cytotoxicity and high biological activity [9]. Several authors have reported a lack of toxic effects that manifest in the forms of inflammation and activation of macrophages [10], and symptoms of systemic toxicity after ND treatment in rats [11,12], but have also noted uptake and intracellular accumulation of NDs [13], activation of cell death (both apoptotic and necrotic) [14], and redox homeostasis disorders [15]. Diamond nanoparticles were also tested for their application in cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nanodiamonds have been considered to be relatively nontoxic in comparison with other carbon nanoparticles. However, as shown in our earlier studies, hydrophobic, hydrogen-terminated and positively-charged diamond nanoparticles can enter the cells, impair their growth and cause cell death [152,156]. The mechanism of cell damage by nanodiamonds is by generating ROS, and by excessive delivery of sodium ions adsorbed on the nanodiamond surface [168].…”
Section: Potential Cytotoxicity and Immunogenicity Of Nanocellulose/nmentioning
confidence: 70%
“…Diamond is an allotrope of carbon, consisting of carbon atoms arranged in a cubic crystal structure covalently bonded in sp 3 hybridization (Figure 4a). Like all nanostructured materials, nanodiamonds or diamond nanoparticles are defined as features not exceeding 100 nm in at least one dimension, although some larger diamond particles, i.e., 125-210 nm, are still referred to as nanodiamonds (for a review, see [152]). At the same time, the size of ultrananocrystalline diamond particles is 3-5 nm [153,154].…”
Section: Characterization Of Nanodiamondmentioning
confidence: 99%
See 2 more Smart Citations